2018
DOI: 10.1055/a-0754-5586
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA Class II Alleles and Haplotypes with Type 1 Diabetes in Tunisian Arabs

Abstract: The molecular association of HLA class II with type 1 diabetes (T1DM) was investigated in Tunisian Arabs using 3 kinds of analyses. The first was a case-control association study, using Relative Predispositional Effects method, involved 137 T1DM cases and 258 control subjects. The second was family-based association-linkage study, using Transmission Disequilibrium Test, and covering 50 Tunisian families comprising 73 T1DM patients and 100 parents. The third was a wide correlation study between 4 DRB1 alleles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…45 HLA class II allele frequency in the samples from self-identified Tunisian Arab women is consistent with prevalence rates reported earlier. 11,18,46 This study demonstrated a significant association of specific DRB1* or protective aspect to these alleles, respectively. This was in evident disagreement with studies on Brazilian, 47 Danish, 37,48 Japanese, 49 Kazakh, 40 and South Indian 25 women, which demonstrated the association of other DRB1 alleles with an increased risk of RPL, namely, DRB1*03:01:01, and DRB1*07/*07.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…45 HLA class II allele frequency in the samples from self-identified Tunisian Arab women is consistent with prevalence rates reported earlier. 11,18,46 This study demonstrated a significant association of specific DRB1* or protective aspect to these alleles, respectively. This was in evident disagreement with studies on Brazilian, 47 Danish, 37,48 Japanese, 49 Kazakh, 40 and South Indian 25 women, which demonstrated the association of other DRB1 alleles with an increased risk of RPL, namely, DRB1*03:01:01, and DRB1*07/*07.…”
Section: Discussionmentioning
confidence: 50%
“…12,16 HLA alleles and respective haplotypes were shown previously to be selectively distributed according to ethnic/racial background, 10,11,17 and to (positively or negatively) influence the disease outcome of several immune and inflammatory disorders. 13,18,19 In particular, a remarkable association between specific class II alleles and corresponding haplotypes with disorders of immunity was noted. This was highlighted by the positive association of DRB1*03:01:01 and DQB1*02:01:01, and the negative association of DRB1*11:01:01 and DQB1*03:01:01 with autoimmune type 1 diabetes, 20 and the powerful association of DRB1*04-DQB1*03 haplotype with increased risk to rheumatoid arthritis.…”
mentioning
confidence: 99%
“…The absence of IAA analysis was a limitation in our study because we could not know whether diabetes in this young age group presented this Ab or if it corresponded to monogenic diabetes. For that, HLA-typing should be tested to confirm the autoimmune origin of T1D in these children [ 43 ], and the extended family history of type 1 diabetes must be considered [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…More or less long extended HLA haplotypes have been studied with some success in certain diseases; Berger's Disease in 1984 [163], type I diabetes in 1992 [164], and some extended HLA haplotypes were also defined in 1991 [165]. However, relatively few studies have been done up until now; some of them were in microscopic polyangiitis [166], celiac disease [167], kidney disease [168,169], diabetes [170], and psoriatic arthritis [171]. Technical difficulties of this type of study may be in part overcome by nowadays more advanced technologies.…”
Section: Hla Haplotypes and Disease Associationmentioning
confidence: 99%